ANALISIS SIFAT KIMIA TANAH DAN KANDUNGAN MINYAK SERAI WANGI (Cymbopogon winterianus Jowitt ) DISERTAI UJI HEDONIK YANG DIPRODUKSI OLEH KELOMPOK TANI KARYATANI DESA SIDORUKUN, KECAMATAN PANGKATAN, KABUPATEN LABUHANBATU - Satria Sir Hidayatullah; Badrul Ainy Dalimunthe; Siti Hartati Yusida Saragih; Fitra Syawal Harahap (UNIVERSITAS LABUHANBATU, 2021)
Fragrant lemongrass (Cymbopogon winterianus Jowitt) is one of the volatile oil-producing plants With high economic value, about 80% of citronella oil produced by Indonesia is exported to various countries. Citronella oil is multi-useful in the pharmaceutical industry and in the perfume industry as a fragrance in various perfumed oil products. This study aims to determine the chemical properties of the soil in the field of citronella farmer group, Sidorukun Village, to determine the citronellal content, oil content and specific gravity of citronella oil meet the requirements set out in the Indonesian National Standard (SNI). And the hedonic test to find out the community's response to citronella oil. This research was carried out from March 2021 to May 2021. The results of the analysis of chemical properties in 2 different locations showed that low soil chemical properties affected the growth and yield of citronella. The analysis of citronella oil showed that the citronella content, oil content and specific gravity of citronella oil (Cymbopogon winterianus Jowitt) produced by the Karyatani Farmers' Group in Sidorukun Village were 41.32%, 0.87% and 0.8881, respectively. This shows that the citronellal content of min 35%, oil content of 0.60% and specific gravity of 0.880-0.922 has met SNI 06-3953-1995, the duration of distillation is an important factor for the high yield of citronellal content, oil content and specific gravity. The hedonic test showed that the color of citronella oil was very liked by the panelists, as well as the smell of citronella oil, the panelists liked it and the taste of citronella oil when applied to the panelists' skin, they liked it and some thought it was normal.Key words: Essential Oils, Citronella, Soil Chemical Properties, Hedonic Test